A Scott transformer based single to three phase power converter for SWER applications - Wolfs, Peter (2013)
Three phase power, especially for pumping applications, is highly desired in many rural applications. For economic reasons, many of these installations are supplied from single phase medium voltage networks. This paper shows that a well-balanced three phase supply, suitable for induction machine supply, can be produced with a Scott transformer connection of a single phase inverter and the existing single phase supply. The single phase converter only processes half of the load power. A regulation scheme based in the DQ frame is proposed and it is shown the single phase inverter directly controls the quadrature axis voltage. A well balanced supply can be produced by regulating this inverter to eliminate any negative sequence voltages. © 2013 Australasian Committee for Power Engineering (ACPE).